Towards a critical and active citizenship in architectural education - Noble, Alexandra (Critical Studies in Teaching and Learning, 2025)
This paper examines how architectural technology education can actively promote social justice, critical engagement, and ethical practice beyond the discipline’s technical focus. Situated within South Africa’s socio-political-spatial context and the enduring legacies of colonialism and apartheid, it focuses on an Architectural Technology Extended Curriculum Programme at a University of Technology, using posthuman and decolonial frameworks from the author’s PhD research. The paper further advances socially just architectural pedagogies by integrating Professor Elmarie Costandius’ concepts of critical and active citizenship, emphasising the role of education in fostering engaged, socially aware practitioners. Through processual learning, event-based pedagogies, and walking excursions, the programme deepens students’ understanding of Cape Town’s urban layout and histories of spatial injustice. These methods aim to enhance students’ critical thinking, encouraging them to become socially responsive practitioners who challenge spatial inequalities and advocate for inclusive design.